Isolation and characterization of the bacteria isolated from pigeon droppings in Pekan Kuala Pilah / Nor Hasmila Mohd Nazri - Mohd Nazri, Nor Hasmila (Faculty of Applied Sciences, 2015)
The aim of this study is to isolate and characterize the isolated bacteria from pigeon droppings. The pigeons is abundance in Kuala Pilah town and the droppings may affect human health. The pigeon has been identified based on the morphology such as body length, color and their gathering types. The sample of droppings was collected using ‘catch and release’ method. This method can ensure the droppings were from the pigeons. The bird droppings were proceed with a serial dilution, streaking on nutrient agar and subculture process. The biochemical tests were performed on each pure sample of bacteria after the subculture process. Gram staining was done to each sample for gram identification before continue with biochemical tests. The tests involved identification purpose were MacConkey, Eosin-methylene blue, Citrate Utilization, Triple Sugar Iron and Hydrogen Sulfide test. Successfully isolated bacteria were Escherichia coli, Klebsiella sp. and Shigella sp. As a conclusion, there are presence of bacteria from pigeon droppings in Kuala Pilah that could affect human health.